New records of the brittle stars Ophiothela venusta and Ophiactis modesta (Echinodermata: Ophiuroidea) from the northern Persian Gulf, with morphological details - Peyghan, Soroor; Doustshenas, Babak; Nabavi, Mohammad Bagher; Rounagh, Mohammad Taghi; Larki, Amir Ashtari; Stöhr, Sabine (Zootaxa, 2018)
During a faunistic survey on two shipwrecks in the northern Persian Gulf, several species of ophiuroid were collected in 2015 and 2016. Ophiactis modesta is reported for the first time in the Persian Gulf and Ophiothela venusta is re-described, because it has likely been misidentified in the past, possibly confused with Ophiopsammium semperi. Both species were epizoic: Ophiothela venusta was found on octocorals, Ophiactis modesta on sponges. Ophiothela venusta is characterized by often bright and striking colour patterns with banded arms and large irregular patches on the disc, varying between combinations of yellow, red, blue, orange, black and grey. Its dorsal disc and arms are covered by rugose granules that vary in size and density. In comparison, O. semperi has a denser cover of smaller granules and a subdued uniform colouration. Ophiactis modesta is a hexamerous, fissiparous species that may be mistaken for Ophiactis savignyi. It can be distinguished by its large round to oval oral papilla and its smaller radial shields.